2021
DOI: 10.3390/rs13224686
|View full text |Cite
|
Sign up to set email alerts
|

Sea Ice Monitoring with CFOSAT Scatterometer Measurements Using Random Forest Classifier

Abstract: The Ku-band scatterometer called CSCAT onboard the Chinese–French Oceanography Satellite (CFOSAT) is the first spaceborne rotating fan-beam scatterometer (RFSCAT). This paper performs sea ice monitoring with the CSCAT backscatter measurements in polar areas. The CSCAT measurements have the characteristics of diverse incidence and azimuth angles and separation between open water and sea ice. Hence, five microwave feature parameters, which show different sensitivity to ice or water, are defined and derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Moreover, the root-mean-square (RMS) errors of CSCAT-derived wind vectors are of the order of 1.2~1.3 m/s (speed) and 12~20 • (direction) as compared to the buoy measurements or the European Centre for Medium-Range Weather Forecasts (ECMWF) winds [1,4]. As such, the CSCAT data have been used in a variety of applications, such as sea-ice monitoring [5,6], regional data assimilation [7], air-sea interaction study [8,9], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the root-mean-square (RMS) errors of CSCAT-derived wind vectors are of the order of 1.2~1.3 m/s (speed) and 12~20 • (direction) as compared to the buoy measurements or the European Centre for Medium-Range Weather Forecasts (ECMWF) winds [1,4]. As such, the CSCAT data have been used in a variety of applications, such as sea-ice monitoring [5,6], regional data assimilation [7], air-sea interaction study [8,9], etc.…”
Section: Introductionmentioning
confidence: 99%
“…There are several advantages to using RFC in remote sensing applications, including the handling of a large number of variables, identifying missing data and outliers, providing unbiased estimates of out-of-bag errors, optimizing feature space using variable importance functions, and being relatively robust to noise and outliers. Thus, RFC has been previously used in sea ice extent monitoring and sea ice classification [78][79][80].…”
Section: Random Forest Classifiermentioning
confidence: 99%
“…The training and testing accuracy of the five methods are shown in Table 3. Zhai et al [78] compared the five classifiers in sea ice extent monitoring using scatterometer observations, and found that RFC exhibits the highest overall accuracy. Our results are consistent with those of [78].…”
Section: Random Forest Classifiermentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the sea ice detection (or sea ice and open water discrimination) methods for satellite scatterometers are mainly classified into two different types, i.e., the physics-based methods and the machine-learning-based methods [7,8]. Both are based on the contrasting scattering properties between sea ice and open water.…”
Section: Introductionmentioning
confidence: 99%